Recolonization by nematodes of hot water treated cooking banana planting material in Uganda - Elsen, A.; Goossens, B.; Belpaire, B.; Neyens, A.; Speijer, P.; Waele, D. de (2004)
In East Africa, the cooking bananas (Musa spp., AAA group, subgroup Matoke) are the major food crop. Yields are decreasing due to increasing damage caused by a complex of pests and diseases, including plant-parasitic nematodes. Planting of infected material is the principle means of dispersal for these nematodes. An option to control the nematodes in planting material is hot water treatment but the benefits depend on the rate of recolonisation. Therefore, on-farm trials were carried out at five localities representing Musa production systems in Uganda. Hot water treatment of planting material slowed down build-up of Radpholus similis at least until 30 months after planting. This was not only the case for the treated mother plants but also for the suckers that developed from these mother plants. A similar trend was observed for Helicotylenchus multicinctus. Hot water treatment also slowed down the build-up of Pratylenchus goodeyi but this effect was less pronounced.